The Impact of Transformational and Transactional Leadership Styles on Employee Performance: A Quantitative Study in the Information Technology Sector - Ghulam Haider; Mehvish Manzoor (JELM, 2025)
This empirical study examines the correlation between employee performance and two prevalent leadership styles transformational and transactional in the Information Technology (IT) sector. The leadership strategies implemented by management frequently have an impact on employee performance, which is a critical determinant of organizational success. The data was collected from 150 IT professionals from a variety of companies using standardized questionnaires, as part of a quantitative, correlational research design. Self-reported employee performance was assessed using a self-developed, validated scale, while perceptions of leadership styles were assessed using the Multifactor Leadership Questionnaire (MLQ 5X-short). A statistically significant positive association between transformative leadership and employee performance was found through data analysis utilizing multiple regression and Pearson correlation (r = 0.72, p < 0.01). There was also a positive, albeit smaller, link with transactional leadership (r = 0.35, p < 0.01). According to a regression study, transformational leadership outperformed transactional leadership as a predictor of performance (β = 0.65, p < 0.001) (β = 0.20, p < 0.05). The results indicate that although both leadership philosophies work, companies in the fast-paced IT industry should give managers' transformational leadership skills top priority in order to boost worker productivity, engagement, and creativity. By offering quantifiable data unique to the industry to direct leadership development initiatives, this study adds to the body of information already in existence.